Dissociative Effects of Neuropeptide S Receptor Deficiency and Nasal Neuropeptide S Administration on T-Maze Discrimination and Reversal Learning - Ahmet Oguzhan Bicakci; Pei-Ling Tsai; Evelyn Kahl; Dana Mayer; Markus Fendt (MDPI AG, 2021)
Cognitive flexibility refers to the ability to modify learned behavior in response to changes in the environment. In laboratory rodents, cognitive flexibility can be assessed in reversal learning, i.e., the change of contingencies, for example in T-maze discrimination learning. The present study investigated the role of the neuropeptide S (NPS) system in cognitive flexibility. In the first experiment, mice deficient of NPS receptors (NPSR) were tested in T-maze discrimination and reversal learning. In the second experiment, C57BL/6J mice were tested in the T-maze after nasal administration of NPS. Finally, the effect of nasal NPS on locomotor activity was evaluated. NPSR deficiency positively affected the acquisition of T-maze discrimination but had no effects on reversal learning. Nasal NPS administration facilitated reversal learning and supported an allocentric learning strategy without affecting acquisition of the task or locomotor activity. Taken together, the present data show that the NPS system is able to modulate both acquisition of T-maze discrimination and its reversal learning. However, NPSR deficiency only improved discrimination learning, while nasal NPS administration only improved reversal learning, i.e., cognitive flexibility. These effects, which at first glance appear to be contradictory, could be due to the different roles of the NPS system in the brain regions that are important for learning and cognitive flexibility.